Calcium transfer and mass balance associated with soil carbonate in a semi‐arid silicate watershed (North Cameroon): An overlooked geochemical cascade?. (16th February 2021) - Dietrich, Fabienne; Diaz, Nathalie; Deschamps, Pierre; Sebag, David; Verrecchia, Eric P.
A bstract: Calcium is a key element of the Earth system and closely coupled to the carbon cycle. Weathering of silicate releases Ca, which is exported and sequestered in oceans. However, pedogenic calcium carbonate constitutes a second Ca‐trapping pathway that has received less attention. Large accumulations of pedogenic calcium carbonate nodules, associated with palaeo‐Vertisols, are widespread in North Cameroon, despite a carbonate‐free watershed. A previous study suggested that a significant proportion of Ca released during weathering was trapped in palaeo‐Vertisols but the pathways involved in the transfer of Ca from sources (the granite and the Saharan dust) to a temporary sink (the carbonate nodules) remain unclear. This study aims to compare the distribution of elements in carbonate nodules and their associated past and present compartments for Ca in the landscape. These compartments are all characterised by a distinctive geochemical composition, resulting from specific processes. Three end members have been defined based on geochemical data: (a) the granite and its residual products, dominated by K2 O and Na2 O, Ti and Zr, HREE, and a positive Ce anomaly; (b) the soil parental material and the Saharan dust, dominated by Al2 O3, Fe2 O3 and MgO, V, HREE, and a positive Ce anomaly; and finally (c) the carbonate nodules, which are dominated by CaO, a depletion in V, Ti and Zr, and an enrichment in REE with a negative Ce anomaly. Mass balance calculations in soil profiles demonstrated that the accumulation of Ca in carbonate nodules exceeds the Ca released by chemical weathering of the parental material, because of a continuous accumulation and contribution from lateral transfers. Consequently, at the landscape scale, carbonate nodules associated with palaeo‐Vertisols constitute a temporary sink for Ca. Such a spatial relationship between sources and transient compartments opens an avenue to the new concept of 'geochemical cascade', similar in terms of geochemistry, to the concept of 'sediment cascade' developed by continental sedimentologists.